Impact of thinning on quantitative characteristics of Brant`s oak (Quercus brantii Lindl.) in Khorramabad Forests - Dariush Mehdifar; Mehdi Pourhashemi; Reza Karamian (تحقیقات جنگل و صنوبر ایران, 2014)
This research aims at exploring 1) change in growth form in young coppice stands of Brant`s oak (Quercus brantii Lindl.) and 2) decrease in competition among individual sprouts in a sprout-clump as imposed by gradual thinning operation. We assessed the effect of different thinning treatments on growth of Brant`s oaks in Chegeni region-Khorram Abad along a 16-year period. The results of the first 4-years are presented here. Four thinning including increasing, decreasing, traditional and control treatments were established, each with 3 replications. The intensity of thinning in decreasing treatment was 32% of all sprouts in a sprout-clump. This was decreased in the next phases to 28%, 22% and 18%, respectively. The trend in the increasing treatment was vice versa. In traditional treatment, all sprouts except 1 to 2 in a sprout-clump were removed. The control treatment included no intervention. Prior to thinning, quantitative characteristics of sample trees were measured. In the last year of research, the measurements were repeated. The results showed that decreasing treatment imposed a considerably positive impact on growth in crown area and diameter of sprouts within the sprout clumps. In addition, traditional treatment was most influential in height growth of sprouts. This study proved the positive effect of thinning on quantitative characteristics of Brant`s oak. Furthermore, it showed that the more intensive the treatments are, the more positively they effect. As a conclusion, thinning operations can improve the unsustainable structural characteristics of young coppice stands within similar sites in Zagros forests of Iran.